Scarlet fever-like outcomes of hand, foot, and mouth disease. - Milano, A. (European Journal of Pediatric Dermatology, 2018)
Hand-foot-mouth disease is a frequent primary viral infection usually caused by Coxsackie A16 or enterovirus A71 and clinically characterized by mouth and pharyngeal vesicles, palmo-plantar papular vesicles and mild fever arising prevalently in summer. For about a decade, epidemics of a more severe form of hand, foot and mouth disease caused by Coxsackie A6, occurring in winter (2), affecting not only children but also adults with intra-family transmission have been described worldwide. In this form the general symptoms are more serious and from a clinical point of view in adults the dorsal surfaces of the hands and feet and the face are affected as in our case. Another clinical feature is periungual and palmo-plantar desquamation (1) which may be with wide flaps, scarlet-fever like as in the present case. The characteristic onychomadesis is due to a lesion of the nail plate induced by the replication of Coxsackie A6 (1).